Too poor to science: How wealth determines who succeeds in STEM. - Craig R McClain (PLoS Biology, 2025)
STEM is profoundly shaped by wealth, yet financial privilege is rarely acknowledged in discussions of diversity and inclusion. Wealth influences participation, persistence, and recognition in science, affecting not just who enters the pipeline but also who can afford to stay.